The Role of Thyme (Zataria multiflora Boiss) Essential Oil as Natural Antioxidant on the Lipid Oxidation in Mayonnaise. (13th April 2022) - Ahmadi-Dastgerdi, Asiye; Fallah, Neda; Zokaei, Maryam; Gholami-Ahangaran, Majid
Abstract : Nowadays, essential oils are considered substitutes for synthetic additives in food products. Since lipid oxidation is the main chemical process affecting mayonnaise deterioration, in this research, the antioxidant activity of essential oil of thyme ( Zataria multiflora Boiss) was determined for oxidative stability of treated mayonnaise (homogenized) during 6 months of storage. The antioxidant activities of the essential oil of thyme (0–150  μ g/g) were investigated by the DPPH method. Then, the efficiency of this essential oil (144.4  μ g/g) as a natural antioxidant in mayonnaise was studied by following analysis: peroxide, anisidine, Totox, and thiobarbituric acid. GC analysis of the essential oil resulted in the identification of forty compounds. The essential oil is characterized by a high number of monoterpenes such as thymol and carvacrol. Regarding antioxidation, the investigated essential oil strongly reduced the DPPH radical (IC50  = 144.4  μ g/ml). This study confirms that the essential oil of thyme possessed antioxidant properties in vitro . The results showed that the treatments containing essential oil and TBHQ significantly reduced the oxidation (p < 0.05 ), while the control sample was oxidized faster. The essential oil had a significant effect on taste, odor, and overall acceptance, but no significant difference was observed in color and texture. The results of the present experiments suggest that essential oil of thyme ( Z. multiflora ) can be used as a source of natural antioxidant for the application in food industries to prevent lipid oxidation particularly lipid-containing foods such as mayonnaise. Therefore, it can used as a natural antioxidant and flavoring compound in foods such as mayonnaise.